2012
DOI: 10.1128/jvi.05949-11
|View full text |Cite
|
Sign up to set email alerts
|

Multiple Layers of CD80/86-Dependent Costimulatory Activity Regulate Primary, Memory, and Secondary Lymphocytic Choriomeningitis Virus-Specific T Cell Immunity

Abstract: The lymphocytic choriomeningitis virus (LCMV) system constitutes one of the most widely used models for the study of infectious disease and the regulation of virus-specific T cell immunity. However, with respect to the activity of costimulatory and associated regulatory pathways, LCMV-specific T cell responses have long been regarded as relatively independent and thus distinct from the regulation of T cell immunity directed against many other viral pathogens. Here, we have reevaluated the contribution of CD28-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
35
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 32 publications
(40 citation statements)
references
References 83 publications
(186 reference statements)
3
35
0
Order By: Relevance
“…Early during infection, STIM1 and STIM2 were required for the differentiation of naive CD8 + T cells into fully functional cytolytic effector cells and mediated the production of cytokines and prevented cellular exhaustion in viral-specific CD8 + effector T cells. [33][34][35][36][37][38][39][40][41] . The total numbers of NP 396-404 -and GP [33][34][35][36][37][38][39][40][41] -specific CD8 + T cells were comparable in DKO and WT mice 8 and 35 days p.i., but were moderately reduced 60 days p.i.…”
Section: +mentioning
confidence: 99%
See 4 more Smart Citations
“…Early during infection, STIM1 and STIM2 were required for the differentiation of naive CD8 + T cells into fully functional cytolytic effector cells and mediated the production of cytokines and prevented cellular exhaustion in viral-specific CD8 + effector T cells. [33][34][35][36][37][38][39][40][41] . The total numbers of NP 396-404 -and GP [33][34][35][36][37][38][39][40][41] -specific CD8 + T cells were comparable in DKO and WT mice 8 and 35 days p.i., but were moderately reduced 60 days p.i.…”
Section: +mentioning
confidence: 99%
“…To understand whether recrudescence of LCMV was due to impaired viral clearance during acute infection, we analyzed the cytotoxic function of DKO CD8 + T cells. CD8 + T cells from WT and DKO P14 mice (which express a transgenic LMCV-specific TCR) were cocultured with LCMV GP [33][34][35][36][37][38][39][40][41] peptide-pulsed target cells. We observed that DKO CD8 + T cells were significantly impaired in their ability to kill target cells in vitro (Figure 2A).…”
Section: Stim1 and Stim2 Regulate The Function And Differentiation Ofmentioning
confidence: 99%
See 3 more Smart Citations